Functional significance of subjective response to alcohol across levels of alcohol exposure. (10th August 2015) - Bujarski, Spencer; Hutchison, Kent E.; Prause, Nicole; Ray, Lara A.
Abstract: Pre‐clinical neurobiological models of addiction etiology including both the allostatic model and incentive sensitization theory suggest that alcohol consumption among alcohol‐dependent (AD) individuals will be dissociated from hedonic reward as positive reinforcement mechanisms wane in later stage dependence. The aims of this study are to test this claim in humans by examining the relationship between dimensions of subjective responses to alcohol (SR) and alcohol craving across levels of alcohol exposure. Non‐treatment‐seeking drinkers ( n = 205) completed an i.v. alcohol challenge (final target breath alcohol concentration = 0.06 g/dl) and reported on SR and craving. Participants were classified as light‐to‐moderate drinkers (LMD), heavy drinkers (HD) or AD. Analyses examined group differences in SR and craving response magnitude, as well as concurrent and predictive associations between SR domains and craving. At baseline, LMD and AD reported greater stimulation than HD, which carried over post‐alcohol administration. However, stimulation was dose‐dependently associated with alcohol craving in HD only. Furthermore, lagged models found that stimulation preceded craving among HD only, whereas this hypothesized pattern of results was not observed for craving preceding stimulation. Sedation was also positively associated with craving, yet no group differences were observed. In agreement with the prediction of diminished positive reinforcement in alcohol dependence, this study showed that stimulation/hedonic reward from alcohol did not precede craving in AD, whereas stimulation was dose‐dependently associated with and preceded craving among non‐dependent HD. Abstract : Neurobiological theories have characterized addiction as pathological motivation, dissociated from hedonic reward. This study tested this claim in humans by examining the relationship between subjective responses and craving during an i.v. alcohol challenge in light‐to‐moderate drinkers, heavy drinkers or alcohol dependents. Consistent with the prediction of diminished positive reinforcement in dependence, this study showed that stimulation/hedonic reward from alcohol did not predict craving in alcohol dependents, whereas stimulation was dose‐dependently associated with and predicted craving among non‐dependent heavy drinkers.